Syntheses and structures of chiral tri- and tetranuclear Cd(II) clusters with luminescent and ferroelectric properties. (8th January 2015) - Wen, He-Rui; Qi, Ting-Ting; Liu, Sui-Jun; Liu, Cai-Ming; Tang, Yun-Zhi; Chen, Jing-Lin
Abstract : Graphical abstract: Synthesis and characterizations of two couples of chiral tri- and tetranuclear Cd(II) complexes reveal that1 and2 are a couple of tetranuclear Cd(II) complex enantiomers crystallized in the chiral space group P 42 22, while3 and4 are a couple of trinuclear Cd(II) complex enantiomers crystallized in the chiral space group P 21 . The circular dichroism further confirmed that1 and2, and3 and4 are a pair of enantiomers, respectively. The strong fluorescence emissions were observed in1 –4, and3 exhibits the ferroelectric behavior. Abstract: Two couples of chiral tri- and tetranuclear Cd(II) clusters, namely [Cd4 ( S -L 1 )6 ]·(ClO4 )2 (1 ) and [Cd4 ( R -L 1 )6 ]·(ClO4 )2 (2 ), and [Cd3 ( S -L 2 )4 ]·(ClO4 )2 (3 ) and [Cd3 ( R -L 2 )4 ]·(ClO4 )2 (4 ) (L 1  = 1-(1-(2-pyridine)-ethylimino)-2-naphtho, L 2  = 2- (1-(2-pyridine)-ethylimino)-5-bromo-6-methoxy-pheno) have been synthesized via the solution reaction of chiral Schiff-base ligands with Cd(ClO4 )2 ·6H2 O, and characterized by single-crystal X-ray analyses, IR and circular dichroism (CD) spectra. Complexes1 and2 are a couple of tetranuclear Cd(II) complex enantiomers crystallized in the chiral space group P 42 22, and3 and4 are also a couple of trinuclear Cd(II) complex enantiomers crystallized in another chiral space group P 21 . The CD measurements further confirmed that1 –2, and3 –4 are a pair of enantiomers with Cotton effects of the opposite sign at the same wavelengths, respectively. The strong solid-state fluorescence emissions were observed at around 465 nm for1 and2, and 485 nm for3 and4, respectively. Furthermore, complex3 exhibits a ferroelectric behavior related to the polar point group C 2 .